Synthesis of six-membered silacycles by borane-catalyzed double sila-Friedel–Crafts reaction - Dong, Yafang; Sakai, Masahiko; Fuji, Kazuto; Sekine, Kohei; Kuninobu, Yoichiro (Beilstein Journal of Organic Chemistry, 2020)
We have developed a catalytic synthetic method to prepare phenoxasilins. A borane-catalyzed double sila-Friedel–Crafts reaction between amino group-containing diaryl ethers and dihydrosilanes can be used to prepare a variety of phenoxasilin derivatives in good to excellent yields. The optimized reaction conditions were also applicable for diaryl thioethers to afford their corresponding six-membered silacyclic products. The gram-scale synthesis of a representative bis(dimethylamino)phenoxasilin and the transformation of its amino groups have also been demonstrated.
Keywords: borane; cyclic compound; organosilane; sila-Friedel–Crafts; silylation

(untitled) - Li, J.; Ding, D.; Wei, Y.; Zhang, J.; Xu, H. (Adv. Opt. Mater., 2016)

(untitled) - Hayashi, H.; Nakao, H.; Miyabayashi, T.; Murase, M. (Jpn. J. Appl. Phys., 2013)

(untitled) - Sun, J. W.; Baek, J. Y.; Kim, K.-H.; Moon, C.-K.; Lee, J.-H.; Kwon, S.-K.; Kim, Y.-H.; Kim, J.-J. (Chem. Mater., 2015)

(untitled) - Matsuo, K.; Yasuda, T. (Chem. Sci., 2019)

(untitled) - Kranenburg, M.; van der Burgt, Y. E. M.; Kamer, P. C. J.; van Leeuwen, P. W. N. M.; Goubitz, K.; Fraanje, J. (Organometallics, 1995)

(untitled) - Kranenburg, M.; Kamer, P. C. J.; van Leeuwen, P. W. N. M. (Eur. J. Inorg. Chem., 1998)

(untitled) - van der Veen, L. A.; Keeven, P. H.; Schoemaker, G. C.; Reek, J. N. H.; Kamer, P. C. J.; van Leeuwen, P. W. N. M.; Lutz, M.; Spek, A. L. (Organometallics, 2000)

(untitled) - Bronger, R. P. J.; Kamer, P. C. J.; van Leeuwen, P. W. N. M. (Organometallics, 2003)

(untitled) - Clayden, J.; Fletcher, S. P.; Senior, J.; Worrall, C. P. (Tetrahedron: Asymmetry, 2010)

(untitled) - Rajesh, K.; Dudle, B.; Blacque, O.; Berke, H. (Adv. Synth. Catal., 2011)

(untitled) - Corey, J. Y.; Corey, E. R.; Chang, V. H. T.; Hauser, M. A.; Leiber, M. A.; Reinsel, T. E.; Riva, M. E. (Organometallics, 1984)

(untitled) - Betson, M. S.; Clayden, J.; Worrall, C. P.; Peace, S. (Angew. Chem., Int. Ed., 2006)

(untitled) - Betson, M. S.; Clayden, J. (Synlett, 2006)

(untitled) - Braddock-Wilking, J.; Corey, J. Y.; French, L. M.; Choi, E.; Speedie, V. J.; Rutherford, M. F.; Yao, S.; Xu, H.; Rath, N. P. (Organometallics, 2006)

(untitled) - Oita, K.; Gilman, H. (J. Am. Chem. Soc., 1957)

(untitled) - Hitchcock, C. H. S.; Mann, F. G.; Vanterpool, A. (J. Chem. Soc., 1957)

(untitled) - Gilman, H.; Miles, D. (J. Org. Chem., 1958)

(untitled) - Gilman, H.; Trepka, W. J. (J. Org. Chem., 1961)

(untitled) - Gilman, H.; Trepka, W. J. (J. Org. Chem., 1962)

(untitled) - Belsky, V. K.; Saratov, I. E.; Reikhsfeld, V. O.; Simonenko, A. A. (J. Organomet. Chem., 1983)

(untitled) - Corey, J. Y.; Trankler, K. A.; Braddock-Wilking, J.; Rath, N. P. (Organometallics, 2010)

(untitled) - Wittenberg, D.; McNinch, H. A.; Gilman, H. (J. Am. Chem. Soc., 1958)

(untitled) - McCarthy, W. Z.; Corey, J. Y.; Corey, E. R. (Organometallics, 1984)

(untitled) - van der Boon, L. J. P.; Hendriks, J. H.; Roolvink, D.; O'Kennedy, S. J.; Lutz, M.; Slootweg, J. C.; Ehlers, A. W.; Lammertsma, K. (Eur. J. Inorg. Chem., 2019)

(untitled) - Onoe, M.; Morioka, T.; Tobisu, M.; Chatani, N. (Chem. Lett., 2013)

(untitled) - Li, H.; Wang, Y.; Yuan, K.; Tao, Y.; Chen, R.; Zheng, C.; Zhou, X.; Li, J.; Huang, W. (Chem. Commun., 2014)

(untitled) - Sato, Y.; Takagi, C.; Shintani, R.; Nozaki, K. (Angew. Chem., Int. Ed., 2017)

(untitled) - Bhr, S.; Oestreich, M. (Angew. Chem., Int. Ed., 2017)

(untitled) - Richter, S. C.; Oestreich, M. (Trends Chem., 2020)

(untitled) - Furukawa, S.; Kobayashi, J.; Kawashima, T. (J. Am. Chem. Soc., 2009)

(untitled) - Furukawa, S.; Kobayashi, J.; Kawashima, T. (Dalton Trans., 2010)

(untitled) - Arii, H.; Nakabayashi, K.; Mochida, K.; Kawashima, T. (Molecules, 2016)

(untitled) - Curless, L. D.; Ingleson, M. J. (Organometallics, 2014)

(untitled) - Omann, L.; Oestreich, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Chen, Q.-A.; Klare, H. F. T.; Oestreich, M. (J. Am. Chem. Soc., 2016)

(untitled) - Yin, Q.; Klare, H. F. T.; Oestreich, M. (Angew. Chem., Int. Ed., 2016)

(untitled) - Ma, Y.; Wang, B.; Zhang, L.; Hou, Z. (J. Am. Chem. Soc., 2016)

(untitled) - Han, Y.; Zhang, S.; He, J.; Zhang, Y. (J. Am. Chem. Soc., 2017)

(untitled) - Omann, L.; Oestreich, M. (Organometallics, 2017)

(untitled) - Dong, Y.; Takata, Y.; Yoshigoe, Y.; Sekine, K.; Kuninobu, Y. (Chem. Commun., 2019)

(untitled) - Ureshino, T.; Yoshida, T.; Kuninobu, Y.; Takai, K. (J. Am. Chem. Soc., 2010)
See for Rhodium-catalyzed intramolecular C–H silylation for the synthesis of silafluorenes.

(untitled) - Reeves, J. T.; Fandrick, D. R.; Tan, Z.; Song, J. J.; Lee, H.; Yee, N. K.; Senanayake, C. H. (Org. Lett., 2010)